The Governance Performance of Selected Barangays in Highly Urbanized City - Monocay, Michelle D.; Mejica, Maria Nove A. (Philippine Social Science Journal, 2020)
The Philippines has enacted several policies to continually elevate the performance of its governance. As such, the Department of Interior and Local Government (DILG) designed a campaign to improve the delivery of services of the different levels of local government units (LGU). A highly urbanized city in the Province of Negros Occidental is a recipient of several recognitions. However, lingering issues such as high incidence of malnutrition, lack of access to potable water, excessive flooding due to drainage and sewerage problems, and several concerns in solid waste management implementation triggered questions on the eligibility of these awards. Thus, this study investigated the level of governance performance of selected barangays in the areas of social services, peace and order, disaster management, and environment management when taken as a whole and grouped according to income and population. Also, it sought to find out if a significant difference exists in the level of governance performance of the barangay councils when they are grouped mentioned demographics.